2020
DOI: 10.1097/md.0000000000021030
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of arthroscopic single-row and double-row repair in the treatment of rotator cuff tears

Abstract: Background: Single-row (SR) and double-row (DR) techniques are 2 kinds of widely used approaches for the arthroscopic repair of rotator cuff. This retrospective clinical trial was performed to address the question of whether a DR rotator cuff anchor repair gives results superior to a SR anchor repair in clinical outcome scores and complication rates. Methods: This study was performed and reported in accordance with the Strengthening the Reporting of Observational studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…The double-row, transosseous-equivalent construct has shown improved biomechanical strength over that of the single-row repair, 4 but the double-row repair has added cost of more anchors, increases operating room time, and is more technically demanding. 5 Recent systematic reviews and metanalysis of biomechanical literature have shown that factors positively influencing the strength of a repair are the number of sutures used in a repair, use of larger diameter sutures, and use of mattress stitches. 7 We believe the aforementioned technique addresses some of the shortcomings of the double-row repair while incorporating all 3 components found in this review to positively influence the strength of the repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The double-row, transosseous-equivalent construct has shown improved biomechanical strength over that of the single-row repair, 4 but the double-row repair has added cost of more anchors, increases operating room time, and is more technically demanding. 5 Recent systematic reviews and metanalysis of biomechanical literature have shown that factors positively influencing the strength of a repair are the number of sutures used in a repair, use of larger diameter sutures, and use of mattress stitches. 7 We believe the aforementioned technique addresses some of the shortcomings of the double-row repair while incorporating all 3 components found in this review to positively influence the strength of the repair.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as the tear size grows, surgeons are more likely to use more implants to address the tear, which leads to increased costs. 5 In this Technical Note, we describe a technique for repair of a massive rotator cuff tear using a transosseous equivalent, double-row construct with a single medial-row anchor, 5 free FiberTape sutures, and 2 preloaded FiberWire sutures.…”
mentioning
confidence: 99%